EFFECTIVENESS OF GROUP COUNSELING BASED ON SATIR MODEL ON STRESS, BURDEN AND FAMILY FUNCTIONS IN CAREGIVERS OF CHILDREN WITH INTELLECTUAL DISABILITIES - รัตนถิรวรรณ ปรารถนา (Journal of the Psychiatric Association of Thailand, 2021)
Objectives: To study the effects of group counseling based on Satir model and to compare the pre-post levels of stress burden and family function of care giver of intellectual disabilities children. Methods: The research design was a quasi-experimental research with pretest-posttest control group design. The samples were randomly selected from the care giver of children with intellectual disabilities consisted of 47 care givers, recruited using the inclusion criteria. They were assigned to 21 subjects in the control and 26 subjects in the experimental groups. The experiment group participated in the group counseling based on Satir model program by the researcher as the group leader. The activities comprised 8 session, each lasting 90-120 minutes, one a week for 8 weeks. The control group received usual care services. The research instruments were the following: 1) Stress test (ST-20) developed by department of mental health. 2) Zarit burden assessment, Thai version and 3) SCORE-15: Index of family functioning and change. Descriptive statistics, chi-square, paired t-test and independent t-test were used in data analysis. Results: The effects of the program were revealed by the results of this study. The post-test mean scores of stress and burden among the caregivers of intellectual disabilities children in the experimental group was significantly lower than the pre-test score (p<.05). Conversely, in the family function dimension of two groups were not significantly difference at .05 level after program. Conclusion: Group counselling based on Satir model that can effect to stress, burden and family function of care giver of intellectual disabilities children in positive directional.